Estimator's piping man-hour manual - Page, John S. (Houston, TX : Gulf Professional Pub., 1999)
This reference provides reliable piping estimating data including installation of pneumatic mechanical instrumentation used in monitoring various process systems. This new edition has been expanded and updated to include installation of pneumatic mechanical instrumentation, which is used in monitoring various process systems.
Shop fabrication of pipe and fittings -- Field fabrication and erection -- Alloy and non-ferrous fabrication -- Pneumatic mechanical instrumentation -- Underground piping -- Hangers and supports -- Painting -- Patent scaffolding -- Insulation -- Sample estimate -- Technical information.
Includes bibliographical references and index.
Keywords: Pipe fitting -- Estimates -- United States; Labor time; United States; Electronic books